Genetic distance and international migrant selection - Tim Krieger; Laura Renner; Jens Ruhose (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2015)
This paper looks at the effect of the relatedness of two countries, measured by their genetic distance, on educational migrant selection. We analyze bilateral country-level education-specific migration stocks from 85 sending countries to the 15 main destination countries in 2000 and show that country pairs with larger genetic distances exhibit more selected migrant stocks compared to country pairs with smaller genetic distances on average. The effect is driven by country pairs with genetic distances above the median, suggesting that genetic distance must be sufficiently large to constitute a barrier to migration for low-skilled migrants. Results are robust to the inclusion of sending and destination country fixed effects, bilateral control variables, and an instrumental variables approach that exploits exogenous variation in genetic distances in the year 1500.
Keywords: F22; J61; Z1; 330; Genetic Distance; International Migration; Selection; Culture